REALISASI KINERJA PENGAWAS DALAM MEMBINA KOMPETENSI PROFESIONAL GURU - Mohamad Muspawi (Yayasan Literasi Kita Indonesia, 2020)
This study aims to study how to improve teacher performance in Public Elementary Schools in Sarolangun district, specifically in the Resort I area of Pelawan District, Sarolangun Regency. The specific target to be achieved from this study is to determine the performance of school supervisors in fostering the professional competence of Islamic Education teachers. The research method used is descriptive qualitative method, in which the researcher describes the research findings in a narrative and as-is. Data collection techniques that are used are observation, documentation, and interview techniques. To check the validity of the data, the authors conduct perseverance observation, triangulation, member check, audit trail. And to analyze the data the authors conduct data review and reduction, data unitization, data categorization, and data interpretation. The results of the study show that the performance of supervisors in fostering the professional competence of Islamic Education teachers in SD Resort I Pelawan District, Sarolangun District is: 1. Conducting meetings between Islamic Education teachers. 2. Conducting comprehensive guidance on the teacher. 3. Monitor the implementation of classroom learning. 4. Provide reinforcement of learning material to the teachers. While the inhibiting factors are: 1. There is a gap in teacher perception. 2. Lack of supporting facilities.